2017
DOI: 10.1002/ps.4655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of callose deposition in rice regulated by exogenous abscisic acid and its involvement in rice resistance to Nilaparvata lugens Stål (Hemiptera: Delphacidae)

Abstract: Our results demonstrated that exogenous ABA suppressed β-1,3-glucanase and induced synthase activity, and promoted callose deposition. This is an important defense mechanism that prevents BPH from ingesting phloem sap. These studies provide support for an insect-resistance mechanism after ABA treatment and provide a reference for the integrated management of other piercing-sucking pests. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…Moreover, ABA-treated plants had decreased enzyme activity and gene expression of beta-1,3-glucanase but increased enzyme activity and gene expression of callose synthase and foliar callose contents. This is consistent with a previous study showing that a decrease in the hydrolyzing enzyme and an increase in callose synthase resulted in an enhancement of callose accumulation in exogenous ABA-treated rice, which shortened the duration of phloem ingestion of brown planthopper (Liu et al, 2017). Thus, the activation of the ABA signaling pathway increased callose synthase but suppressed callose degradation to accumulate callose in plant tissue, which decreased the phloem feeding of B. tabaci.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, ABA-treated plants had decreased enzyme activity and gene expression of beta-1,3-glucanase but increased enzyme activity and gene expression of callose synthase and foliar callose contents. This is consistent with a previous study showing that a decrease in the hydrolyzing enzyme and an increase in callose synthase resulted in an enhancement of callose accumulation in exogenous ABA-treated rice, which shortened the duration of phloem ingestion of brown planthopper (Liu et al, 2017). Thus, the activation of the ABA signaling pathway increased callose synthase but suppressed callose degradation to accumulate callose in plant tissue, which decreased the phloem feeding of B. tabaci.…”
Section: Discussionsupporting
confidence: 92%
“…Infestation by phloem-sucking insects can increase the ABA content and the expression of ABA signaling-related genes in their host plants (Quintana-Camargo et al, 2015;Hillwig et al, 2016). Furthermore, the importance of ABA signaling in plant resistance to insects has been attributed to its role in inducing foliar callose deposition (Liu et al, 2017). Our results showed that not plants with little callose accumulation had an increased B. tabaci population abundance and phloem-feeding efficiency, while ABA-treated plants with increased callose accumulation maintained a reduced B. tabaci population abundance and phloem-feeding efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several recent computational models have investigated how hormone crosstalk modifies the root-tip auxin pattern via regulation of both auxin transport and synthesis (Moore et al, 2015;Di Mambro et al, 2017); considering how hormone diffusion through plasmodesmata affects the predictions from hormone crosstalk models would further elucidate their role. In addition, several studies have shown that other hormones, such as ABA (Liu et al, 2017a), gibberellic acid (Rinne et al, 2011) and salicylic acid (Wang et al, 2013), regulate plasmodematal gating via regulation of callose deposition, and so as well as hormonal crosstalk on a transcriptional level, future crosstalk models may also need to consider regulation of hormonal movement via plasmodesmata.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it was shown that callose lining of sieve plate pores is essential for normal phloem transport because it confers favorable flow characteristics on the pores, 29 while exogenous ABA has been shown to promote callose deposition. 30 The role of sugars in leaf senescence is actively discussed. Nevertheless, both increased concentration of sugars and their deficit may serve as stimulus for senescence, while accumulation of sugars in the senescent leaf may be not the cause, but the consequence of senescence.…”
Section: Discussionmentioning
confidence: 99%